2013
DOI: 10.1089/ten.tea.2012.0738
|View full text |Cite
|
Sign up to set email alerts
|

Small diameter vascular graft engineered using human embryonic stem cell-derived mesenchymal cells

Abstract: Despite the progress made thus far in the generation of small-diameter vascular grafts, cell sourcing still remains a problem. Human embryonic stem cells (hESCs) present an exciting new cell source for the regeneration applications due to their high proliferative and differentiation capabilities. In this study, the feasibility of creating small-diameter vascular constructs using smooth muscle cells (SMCs) differentiated from hESCderived mesenchymal cells was evaluated. In vitro experiments confirmed the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…small-diameter vascular graft | infrarenal abdominal aorta mouse model | electrospinning | hydrogel | endothelial colony-forming cells T here is a significant need for small-diameter vascular grafts (sdVGs; <6 mm in diameter) for the treatment of various arterial complications, such as coronary artery disease (CAD) and pediatric congenital cardiovascular defects (CCDs). CAD is the leading cause of death or impaired quality of life, resulting in more than half a million coronary artery bypass surgeries per year (1)(2)(3)(4). Meanwhile, pediatric CCDs are present in 1% of live births (5), with most cases requiring repeated surgical reconstruction to maximize long-term survival (5)(6)(7).…”
mentioning
confidence: 99%
“…small-diameter vascular graft | infrarenal abdominal aorta mouse model | electrospinning | hydrogel | endothelial colony-forming cells T here is a significant need for small-diameter vascular grafts (sdVGs; <6 mm in diameter) for the treatment of various arterial complications, such as coronary artery disease (CAD) and pediatric congenital cardiovascular defects (CCDs). CAD is the leading cause of death or impaired quality of life, resulting in more than half a million coronary artery bypass surgeries per year (1)(2)(3)(4). Meanwhile, pediatric CCDs are present in 1% of live births (5), with most cases requiring repeated surgical reconstruction to maximize long-term survival (5)(6)(7).…”
mentioning
confidence: 99%
“…Recent advancements in the development of biomimetic materials and scaffolds have demonstrated that the ability to preserve or replicate the biochemical and mechanical properties of the ECM is key to the retention of appropriate, and in some cases, pathological cell function. 10,28,32,40 Cell derived ECM proteins from whole tissue or that derived from cultured cells are frequently used for experimental investigations of cell response to the microenvironment, and tissue engineering of whole organs, large vessels (arteries and veins) and small blood vessels (arterioles, venules, and capillary structures). In particular, fibroblast and smooth muscle cell (SMC) derived ECM are commonly used in experimental studies and commercial tissue engineered structures, including tissue engineered vascular grafts (TEVG), each requiring an appropriate EC adhesive and proliferative response.…”
Section: Introductionmentioning
confidence: 99%
“…As the field began attempting smaller diameter grafts, neointimal hyperplasia and thrombus formation bedeviled the transplants and many grafts failed either due to insufficient transport properties or biomechanical failure. As these problems surfaced, so did novel biomaterials and combinations with various stem cell components attempting to solve it [74,76]. Investigators have likewise been creating more advanced tissue-engineered vascular grafts utilizing novel bioreactor/culture systems and stem cell sources, including iPSCs [77,78].…”
Section: Stem Cell-derived Vasculature As Cell Therapy and Functiomentioning
confidence: 99%